SELF DISCOVERIES IN THE LITTLE PRINCE BY ANTOINE DE EXUPERY : JUNGIAN ANALYSIS - Shaheila Raihani; Hana Farida (Universitas Duta Bangsa Surakarta, 2026)
Self discovery or individuation is a lifelong process that leads one self into their true self by emerging different elements of their psyche as well as their conscious and unconscious state. Seen through Jungian archetypes, individuation leads to understanding of one self based on self exploration to aim for originality, inner harmony, and maturity. This understanding of the individuation process can be seen in The Little Prince by Antoine de Saint-Exupéry. To assist the young selves, this research focuses on the representation of self discoveries through the journey of the little prince. Through his journey, the little prince also showed self-exploration and understanding by meeting other characters in the story. Using the descriptive qualitative method, this study will focus on the representation of the individuation process in the story of The Little Prince novel. The purpose of this research is to help the young selves to understand the importance of understanding the true meaning of their lives through the representation in The Little Prince novel.